2016
DOI: 10.1186/s40885-016-0052-y
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive response to exercise: mechanisms and clinical implication

Abstract: A hypertensive response to exercise (HRE) is frequently observed in individuals without hypertension or other cardiovascular disease. However, mechanisms and clinical implication of HRE is not fully elucidated. Endothelial dysfunction and increased stiffness of large artery contribute to development of HRE. From neurohormonal aspects, excess stimulation of sympathetic nervous system and augmented rise of angiotensin II seems to be important mechanism in HRE. Increasing evidences indicates that a HRE is associa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
59
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(71 citation statements)
references
References 28 publications
8
59
0
4
Order By: Relevance
“…These groups are well known to be vulnerable for HFpEF; therefore, our results support that HTR is a potential contributor to HFpEF through ventricular‐arterial uncoupling . Although a previous study has shown that HTR is related to renin‐angiotensin system activation our study suggests that exaggerated activation of the sympathetic nervous system also contributes to HTR when considering a higher HR and SBP response to a low‐grade workload, especially in men and older patients. This suggests that HTR can be used to guide individualized antihypertensive medications according to the contributors to HTR such as activation of the sympathetic nervous system or arterial stiffness.…”
Section: Discussionsupporting
confidence: 76%
“…These groups are well known to be vulnerable for HFpEF; therefore, our results support that HTR is a potential contributor to HFpEF through ventricular‐arterial uncoupling . Although a previous study has shown that HTR is related to renin‐angiotensin system activation our study suggests that exaggerated activation of the sympathetic nervous system also contributes to HTR when considering a higher HR and SBP response to a low‐grade workload, especially in men and older patients. This suggests that HTR can be used to guide individualized antihypertensive medications according to the contributors to HTR such as activation of the sympathetic nervous system or arterial stiffness.…”
Section: Discussionsupporting
confidence: 76%
“…In the present study, coronary artery plaque in long-distance runners may be produced by inflammation due to oxidative stress resulting from excessive exercise; runners with EIH are especially exposed to higher exercise intensity than the NBPG, resulting in increased plaque generation; therefore, measures are needed to prevent plaque development in these runners. Specifically, antioxidants [ 23 , 24 ] or antihypertensives, such as angiotensin II receptor blocker, [ 25 ] may be considered, and it may also be necessary to adjust the exercise intensity. However, as precise prevention guidelines are not available to date, large-scale studies are warranted in the future.…”
Section: Discussionmentioning
confidence: 99%
“…Warner et al [ 32 ] reported that the maximum SBP was lowered by 33 mm Hg in patients with exaggerated BP response by angiotensin II receptor inhibitors. Kim and Ha [ 33 ] stated that angiotensin receptor inhibitors or ACE inhibitors can be recommended for patients with EIH. Moreover, Liakos et al reported that angiotensin receptor blocker were effective at suppressing the exercise induced acute phase inflammatory response.…”
Section: Discussionmentioning
confidence: 99%